Unenhanced Dual-Energy Computed Tomography: Visualization of Brain Edema. Issue 2 (February 2018) - Mohammed, Mohammed F.; Marais, Olivia; Min, Adam; Ferguson, David; Jalal, Sabeena; Khosa, Faisal; O'Keeffe, Michael; O'Connell, Tim; Schmiedeskamp, Heiko; Krauss, Bernhard; Rohr, Axel; Nicolaou, Savvas
Abstract : Purpose: The aim of this study was to determine whether dual-energy computed tomography (DECT) imaging is superior to conventional noncontrast computed tomography (CT) imaging for the detection of acute ischemic stroke. Materials and Methods: This was a retrospective, single-center study of 40 patients who presented to the emergency department (ED) of a major, acute care, teaching center with signs and symptoms of acute stroke. Only those patients who presented to the ED within 4 hours of symptom onset were included in this study. All 40 patients received a noncontrast DECT of the head at the time of presentation. Each patient also received standard noncontrast CT of the head 24 hours after their initial presentation to the ED. "Brain edema" images were then reconstructed using 3-material decomposition with parameters adjusted to suppress gray/white matter contrast while preserving edema and increasing its conspicuity. The initial unenhanced, mixed images, brain edema, and 24-hour follow-up true noncontrast (TNC) images were reviewed and assigned Alberta Stroke Program Early CT scores. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: Of the 40 patients, 28 (70%) were diagnosed with an acute infarction. Brain edema reconstructions were better able to predict end infarction volume, with Alberta Stroke Program Early CT scores similar to the 24-hour follow-up TNC CT (7.75 vs 7.7; P > 0.05), whereas the mixed images routinely underestimated the extent of infarction (8.975 vs 7.7; P < 0.001). Initial TNC images had a sensitivity, specificity, PPV, and NPV of 80% (95% confidence interval [CI], 51.9%–95.7%), 72.7% (95% CI, 39%–94%), 80% (95% CI, 51.9%–95.7%), and 72.73% (95% CI, 51.91%–95.67%), respectively. The DECT brain edema images provided a sensitivity, specificity, PPV, and NPV of 93.33% (95% CI, 68.05%–99.83%), 100% (95% CI, 71.51%–100%), 100% (95% CI, 76.84%–100%), and 91.67% (95% CI, 61.52%–99.79%), respectively. There was very good interrater reliability across all 3 imaging techniques. Conclusion: Brain edema reconstructions are able to more accurately detect edema and end-infarct volume as compared with initial TNC images. This provides a better assessment of the degree and extent of infarction and may serve to better guide therapy in the future.